Survey of Image Processing Based Applications in AMR - Karthick, K; Premkumar, M; Manikandan, R; Cristin, R (Review of Computer Engineering Research, 2018)
The ability to use computer and human based interaction would make things easier for the user, but would be challenging for the researchers. More sophisticated imaging systems can handle inter plot the results of image analysis and describe the various objects and their connections in the scene. The electricity, gas, and water metering instruments may employ the Automatic meter reading (AMR) system for automation of bill generation process. The image processing implementation may ease the process of AMR. In this paper, we discussed the image processing applications in AMR.